THE EFFECTIVENESS OF SERVICE ABILITY FOR INTERNSHIP STUDENTS USING THE LEARNING BY DOING METHOD KAI KERTAPATI STATION - Lisa Erlia; Putri Citra Hati (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
Organizational communication is a major alternative in establishing cooperation within the scope of the company's organization. With organizational communication, messages and information are more easily conveyed and understood by both parties concerned. This study aims to describe and explain the important role of personal organizational communication in the Finance Division of PT. Taspen Palembang in collaborating with the Regional Government. In this study using descriptive research methods with qualitative methods. The source of this research data comes from observations and interviews with informants. The secondary data sources come from literature studies, the company's official website, and official document archives. In addition, a theoretical approach is also carried out to facilitate researchers in reviewing problems, the approach uses phenomenological investigations. The results of this study indicate that the Finance Division of PT. Taspen Palembang uses formal and informal communication in collaborating with local governments. With this organizational communication, various obstacles that occur can be overcome, especially in the problem of paying premium bills by the Regional Government and KPPN. Apart from providing formal notification or billing, the Finance Division of PT. Taspen Palembang also communicates intensively through interpersonal communication from staff level employees to Regional Leaders